Sustainable practices for soil conservation in livestock production systems in the high tropics - Luis G. Bautista-Montealegre; Juan C. Benavides-Cruz; William A. Cardona; Paola J. Criollo-Campos; Daniel R. Torres-Cuesta; Luis O. Albarracín-Arias; Martha M. Bolaños-Benavides (Temas Agrarios, 2023)
Livestock in Colombia is carried out in large areas, in 2022 about 633.841 farms and 29.301.392 animals were reported. Traditional systems with low technology generate a negative impact on soils, affecting physical and chemical conditions. Therefore, it is important to implement management alternatives that guarantee sustainability and profitability. Through an alliance between FAO and AGROSAVIA, the effect of the three systems was evaluated during two periods of time: silvopastoral with an arrangement in a strip-grazing pasture (SPS), silvopastoral with grasslands renewal (GRS), and traditional grazing on grasslands (TS), on physical and chemical properties of the soil. A split-plot experimental design was used, a two-way multivariate analysis of variance (two-way MANOVA) was applied (productive system and sampling time), and an analysis of variance (ANOVA) with a 5% Tukey's test. Using the ArcGIS® Pro 2.9.0 (ESRI®) software, the results of the previously georeferenced samplings were interpolated, using the inverse distance weighting technique (IDW) and the Moran's Index, to verify the type of distribution of the variables influenced by the factors. The MANOVA indicated that individual factors had a significant effect on electrical conductivity (EC), Na, and P, and interaction of factors on Fe, Cu, Mn, particle density (PD), and moisture retention (MR). On the other hand, through the ANOVA, significant differences were identified, registering higher EC, P, MR, and lower PD in SPS, higher content of Fe and Mn in GRS and Cu in TS.